New trends in protection of plant breeder’s rights on the example of apple varieties: cultivars as trademarks, clubs and brands - В. М. Меженський; Н. Б. Якубенко (Plant Varieties Studying and Protection)
Purpose. To analyse the world experience and current trends in protection of new apples varieties and plant breeders’ rights.